2022
DOI: 10.3390/atmos13020361
|View full text |Cite
|
Sign up to set email alerts
|

Observed Climatology and Trend in Relative Humidity, CAPE, and CIN over India

Abstract: Water vapor is the most dominant greenhouse gas in the atmosphere and plays a critical role in Earth’s energy budget and hydrological cycle. This study aims to characterize the long-term seasonal variation of relative humidity (RH), convective available potential energy (CAPE), and convective inhibition (CIN) from surface and radiosonde observations from 1980–2020. The results show that during the monsoon season, very high RH values are depicted while low values are depicted during the pre-monsoon season. West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The April and May month also see the increased RH due weights due to the increased thunderstorm activities over east and northeast India leading to increase in the Relative humidity. The relative humidity is seen to have less impact on aggravating impact of heat waves over plains of northwest India and adjoining central India, which is very well correlated with the climatological lower relative humidity values over these regions 41,42 . In the month of June, again the situation is similar to March and April with additional few areas in Vidarbha, southern parts of Rajasthan and adjoining Gujarat showing more impact of RH over Heat Wave.…”
Section: Discussionmentioning
confidence: 80%
“…The April and May month also see the increased RH due weights due to the increased thunderstorm activities over east and northeast India leading to increase in the Relative humidity. The relative humidity is seen to have less impact on aggravating impact of heat waves over plains of northwest India and adjoining central India, which is very well correlated with the climatological lower relative humidity values over these regions 41,42 . In the month of June, again the situation is similar to March and April with additional few areas in Vidarbha, southern parts of Rajasthan and adjoining Gujarat showing more impact of RH over Heat Wave.…”
Section: Discussionmentioning
confidence: 80%
“…An increasing number of studies have shown the significant role of temperature and LAVPD increases in climate‐change‐induced tree mortality and growth decline (Novick et al ., 2016; Grossiord et al ., 2020; Trotsiuk et al ., 2021; McDowell et al ., 2022). Still, uncertainty and potential heterogeneity in the future VPD trend exist, as there are reports of increasing, instead of decreasing, trends in surface RH with warming at regional scales (Singh et al ., 2008; Eludoyin et al ., 2014; Khan et al ., 2022). More importantly, the interconnected nature of temperature and LAVPD complicates efforts to better understand and model plant responses to a changing environment, which highlights the need to disentangle the effects of temperature and LAVPD (Smith et al ., 2020; Schönbeck et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%